2001
DOI: 10.1046/j.1365-2265.2001.01262.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased dopaminergic tone and increased basal bioactive prolactin in men with human immunodeficiency virus infection

Abstract: The raised fasting bioactive PRL, the diminished response of both immunoreactive and bioactive PRL and the absent TSH response to metoclopramide in HIV infected men, suggest the existence of a decreased, but not absent dopaminergic tone. A monomeric form of PRL was the predominant circulating species, as in healthy men, and this hormone seems to be associated both with CD4+ T lymphocytes and the viral load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
2
14
0
1
Order By: Relevance
“…[17] Current postualtion is that HIV infection reduces dopaminergic tone and thereby increases the bioactivity of prolactin, though the machanism of this effect remains unclear. [18]…”
Section: Functional Derangement Of Endocrine Organs: Direct Effect Ofmentioning
confidence: 99%
“…[17] Current postualtion is that HIV infection reduces dopaminergic tone and thereby increases the bioactivity of prolactin, though the machanism of this effect remains unclear. [18]…”
Section: Functional Derangement Of Endocrine Organs: Direct Effect Ofmentioning
confidence: 99%
“…Além disso, a hiperprolactinemia pode estar associada ao surgimento de hipogonadismo central (37). Evidên-cias sugerem aumento da bioatividade da prolactina em pacientes infectados pelo HIV por redução do tônus dopaminérgico nesses pacientes (38). Hiperprolactinemia associada à galactorreia tem ainda sido relatada em usuários de inibidores de protease.…”
Section: Ginecomastia E Hiperprolactinemiaunclassified
“…The diagnosis of HIV infection was confirmed by immunoblot analysis for HIV antibodies, and T cells expressing the CD4 and CD8 molecules were determined by three‐colour flow cytometry using fluorescent specific monoclonal antibodies 29 . Detailed clinical characteristics of the volunteers have been previously published 24 …”
Section: Methodsmentioning
confidence: 99%
“…Despite the overwhelming information regarding the possible role of PRL, especially biologically active PRL, in HIV infection, this area has remained largely unexplored. Nevertheless, some studies have suggested indirectly that the existence of a low DA tone in men with HIV‐infection 21 , 22 , 23 , 24 could represent an adaptive mechanism attempting to stimulate human lymphocyte proliferation at a maximum possible rate in an attempt to survive 25 . The aim of the present study was to explore the in vivo and in vitro production of bioactive PRL in a group of untreated HIV‐infected men and its association with the cell cycle and apoptosis of PBMC in these patients.…”
Section: Introductionmentioning
confidence: 99%